Practical data acquisition for instrumentation and control systems - Park, John, 1953-
* Covers all aspects of the data acquisition system from design and specification to programming, installation and configuration * Gives both the novice and experienced user a solid understanding of interfacing the PC and standalone instruments to real-world signals from the laboratory to the industrial plant * Provides a thorough grasp of PC data acquisition systems and the ability to design, specify, install and configure and program data acquisition systems quickly and effectivelyThis book focuses on data acquisition and control using the PC and standalone instruments. The PC has made a dra.